The use of an interim CEO during succession episodes and firm performance - Ballinger, Gary A.; Marcel, Jeremy J. (Strategic Management Journal, 2010)
Abstract Our study investigates an unexplored succession process—interim CEO successions. We define an interim CEO succession as a case where the title of chief executive officer is vacated by the incumbent and the board of directors has not announced a permanent successor, but instead designates a particular individual as ‘interim CEO,’ or ‘acting CEO,’ or ‘CEO until a permanent successor is named.’ Theory predicts that interim CEO successions will lead to the type of disruption that can harm firm performance, even after a permanent successor is appointed. Our data show that interim CEO succession processes are widely employed by publicly‐traded U.S. firms, and that they are associated with lower performance during the period in which the interim serves. However, whether the interim CEO also simultaneously serves as chairman moderates the impact of this type of succession on firm performance, as well as on long‐term firm survival. Copyright © 2009 John Wiley & Sons, Ltd.